Deciphering a Chilean harvestmen enigma: what is Parabalta bicornis (Gervais, 1849) comb. nov. (Opiliones: Gonyleptidae: Pachylinae) - Acosta, Luis E. (Zootaxa, 2025)
The largely neglected Chilean harvestman Gonyleptes bicornis Gervais, 1849 (Opiliones, Gonyleptidae), hitherto considered a junior synonym of Sadocus asperatus (Gervais, 1847), is revalidated and reallocated in genus Parabalta Roewer, 1913. This species has been repeatedly confused in the early literature, due to the misleading mismatch between text and figures in the original publication, and the lack of types. A thorough comparison of descriptions and figures demonstrated that two drawings displaying G. bicornis were mistakenly referred to G. acanthops Gervais, 1849 (currently species inquirenda and incertae sedis) and G. planiceps Guérin-Méneville in Gervais, 1842 (currently Eubalta planiceps). Parabalta bicornis comb. nov. is hereby redescribed upon modern samples; considering the complexity of the taxonomical problem, a male neotype is accordingly designated. Among other features, males can be distinguished from congeners, P. reedii (Butler, 1874) and P. cristobalia (Roewer, 1943), by the bifid apophysis on coxa IV, a strong finger-like, upwards-pointing apophysis on trochanter IV, and the armature of femur IV. A detailed comparison between these species and an updated distribution map are given.